VvBAP1 Is Involved in Cold Tolerance in Vitis vinifera L. - Hou, Lixia; Zhang, Guangke; Zhao, Fanggui; Zhu, Dan; Fan, Xinxin; Zhang, Zhen; Liu, Xin (Frontiers in Plant Science, 2018)
Low temperature is one of the bottlenecks restricting the growth of the grape industry. Research on the mechanism of cold tolerance in grapes is therefore very important. BAP1 (BON association protein 1) is a recently-discovered phospholipid-binding protein with a C2 protein domain. However, little is known about its function and the underlying mechanism. The VvBAP1 gene was cloned in our previous studies in grapes, and bioinformatics analysis showed that it has the conservative calcium-dependent C2 protein domain. In this study, cold treatment was applied to the cold-resistant grape varieties of ‘F-242’ and ‘Zuoyouhong’, and to the cold-sensitive grape varieties of ‘Cabernet Sauvignon’ and ‘Chardonnay’. The expression level of VvBAP1 in the cold-resistant varieties was significantly higher than that in the cold-sensitive varieties, indicating that VvBAP1 may be correlated with the cold response process in grapes. Using the cold-resistant grape variety ‘F-242’ as the material, cold stress and Ca2+ could induce the expression of VvBAP1. In addition, VvBAP1 was transferred to Arabidopsis to generate ectopic overexpression plants. The physiological index and gene expression were detected under low temperature (4°C and -8°C). The results showed that the activities of superoxide dismutase (SOD) and peroxidase (POD) in these transgenic plants were higher than those in wild type (WT) plants, with cell membrane permeability and malondialdehyde (MDA) content lower than those of WT plants. Meanwhile, the content of soluble sugar and the expression levels of sugar-metabolizing related genes, including BAM4-7, SS4, and G6PD5, were significantly higher than those of WT plants. Furthermore, the expression of low temperature response signal genes, including CBF1, CBF3, COR15a, COR6.6, COR27, and KIN1, were also enhanced. VvBAP1 could strengthen cold resistance in grapes through adjusting and controlling sugar content and activating antioxidant enzyme activity.